Philosophical Approaches to Achieving Inclusive and Equitable Education: Addressing the Challenges of the Education System in Indonesia - Haryadi, Rofiq Noorman; Rohmadi, Yusup; Gusmian, Islah (Pasundan Social Science Development, 2025)
The education system in Indonesia faces complex structural challenges, particularly in the context of disparities in access, quality, and treatment, which ultimately hinder the achievement of the ideal goals of inclusive and equitable education. This study aims to examine in depth how educational philosophy can serve as a fundamental foundation and conceptual framework to transform the education system toward a more inclusive and just model. The approach used is a philosophical-analytical literature review, comparing and analyzing key philosophical schools—such as Progressivism, Social Reconstructionism, and Humanism—in relation to policy and curriculum practices in Indonesia. The findings of the study show that educational philosophy, especially through the lens of Social Reconstructionism, offers a strong ethical and practical framework. This perspective demands that education not only functions to transfer knowledge but also acts as an agent of social change, actively identifying and dismantling systemic injustices (discrimination based on ethnicity, economy, or disability). Inclusive and equitable education is not only understood as providing physical access but also as the restructuring of curriculum, pedagogy, and assessment that values diversity and ensures equal opportunities for every learner. Implementing this idea requires a paradigm shift from a uniform, homogeneous model to a heterogeneous model that accommodates specific needs, as well as strengthening the role of teachers as reflective agents and social activists. The conclusion of this study is that, without a solid philosophical foundation, efforts to reform education in Indonesia will be superficial and patchwork. The approach of educational philosophy is an absolute prerequisite to produce consistent, sustainable policies that are truly oriented towards universal human values, so that the ideals of inclusive and equitable education can be realized in overcoming the existing system's challenges.